A tentative species list of the European herpetofauna (Amphibia and Reptilia) — an update - Speybroeck, Jeroen; Beukema, Wouter; Crochet, Pierre-André (Zootaxa, 2010)
Research on the taxonomy of European amphibians and reptiles has increased noticeably over the last few decades, indicating the need for recognition of new species and the cancellation of others. This paper provides a critical review of recent changes and draws up a tentative species list.